2020
DOI: 10.1056/nejmoa2019014
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxychloroquine with or without Azithromycin in Mild-to-Moderate Covid-19

Abstract: Background Hydroxychloroquine and azithromycin have been used to treat patients with coronavirus disease 2019 (Covid-19). However, evidence on the safety and efficacy of these therapies is limited. Methods We conducted a multicenter, randomized, open-label, three-group, controlled trial involving hospitalized patients with suspected or confirmed Covid-19 who were receiving either no supplemental oxygen or a maximum of 4 liters per minute of supplemental oxygen. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
833
3
54

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 975 publications
(923 citation statements)
references
References 13 publications
33
833
3
54
Order By: Relevance
“…Hydroxychloroquine might increase the risk of adverse events leading to drug discontinuation compared with the other interventions. Notably, this iteration of the living network meta-analysis did not include four recently published randomised controlled trials on hydroxychloroquine compared with standard care 66676873. RECOVERY, the largest randomised controlled trial on hydroxychloroquine, suggests that hydroxychloroquine might not reduce mortality and might increase length of hospital stay 66.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxychloroquine might increase the risk of adverse events leading to drug discontinuation compared with the other interventions. Notably, this iteration of the living network meta-analysis did not include four recently published randomised controlled trials on hydroxychloroquine compared with standard care 66676873. RECOVERY, the largest randomised controlled trial on hydroxychloroquine, suggests that hydroxychloroquine might not reduce mortality and might increase length of hospital stay 66.…”
Section: Discussionmentioning
confidence: 99%
“…One of them also reported no benefit in need for admissions or clinical improvement [37]. The lack of clinical improvement was reported in another trial [38]. Finally, two more RCTs have reported no association between HCQ and virological clearance [39] or prevention of disease in individuals exposed to it [40].…”
Section: Discussionmentioning
confidence: 96%
“…In early February, chloroquine/hydroxychloroquine was reported to have apparent antiviral effect on SARS-CoV-2 11 , and then it was recommend for treatment of COVID-19 patients soon. As the clinical trials continued, chloroquine/hydroxychloroquine didn't exert the clinical effect as people expected 36,37 , thus it was gradually not recommended for use alone. We comprehensively analyzed data of the trials which used chloroquine/hydroxychloroquine and con rmed it did not reduce the mortality signi cantly as compared with standard care.…”
Section: Discussionmentioning
confidence: 99%
“…The screening process was shown in figure 1 and 3860 studies were identified according to the research strategy initially. In total, 22 studies containing 12795 patients were adopted in our study and all of them were published in English 10,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Among trails included, half of them were RCTs, and the other were Non-RCTs.…”
Section: Literature Researchmentioning
confidence: 99%